Efeito da temperatura no cultivo e produção de lipídios microalgais por Phormidium autumnale em vinhaça de cana-de-açúcar - Réco, Aline Sotta (Universidade Federal de São Carlos, 2023)
Microbial oils, known as "unicellular lipids", are becoming a more environmentally friendly option for biodiesel production, since they have technological advantages when compared to vegetable oils. Obtaining biodiesel with adequate properties from microalgae could be made possible through the use of low-cost organic carbon sources, preferably linking the use of agro-industrial by-products, along the lines of a “biorefinery”. Vinasse is the main wastewater from sugarcane processing, generated by the distillation of the solution balanced by fermentation. In the current methods used for alcohol production, for each liter of ethanol produced, approximately 10 liters of vinasse are generated. As it is a byproduct with a high polluting impact and generated at high temperature, its cooling is essential for any use, although it accelerates degradation reactions, degradation through promising microorganisms in the degradation of the molecules of this pollutant, due to their ability to degrade recalcitrant substances present in the residue, due to the production of enzymes that promote high redox potential of organic compound. In this context, the present proposal intends to evaluate the effect of temperature on growth and lipid production by Phormidium autumnale in sugarcane vinasse, with evaluation of the fatty acid profile in microalgal oil. The highest biomass productivity (90 mg L-1h-1) was maintained for the initial period of cultivation in vinasse with progressive cooling, with removals of around 30 to 40% of carbon and evolved from the medium around 72 hours. The oil obtained from the biomass generated showed 59% extraction of saturated fats, 4% of monounsaturated fats and 29% of polyunsaturated fats (PUFAs), and most of the properties of biodiesel were within international standards. The results suggested a potential for obtaining microalgal lipid by Phormidium autumnale grown in sugarcane vinasse in a biorefinery system.
Effect of temperature on the cultivation and production of microalgal oils by Phormidium autumnale in sugarcane vinasse
Keywords: Microalgas; Biodiesel; Vinhaça; Biorrefinaria; Micoalgae; Vinasse; Biorefinery; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::BIOLOGIA E FISIOLOGIA DOS MICROORGANISMOS::MICOLOGIA; CIENCIAS BIOLOGICAS::BIOQUIMICA::METABOLISMO E BIOENERGETICA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; CIENCIAS EXATAS E DA TERRA::QUIMICA